Disproportionality analysis of bullous pemphigoid adverse events with PD-1 inhibitors in the FDA adverse event reporting system. Issue 7 (3rd July 2019) - Aggarwal, Pushkar
ABSTRACT: Objectives : Bullous pemphigoid, an autoimmune dermatological disease, may be associated with the use of a relatively new anti-cancer drug class, PD-1 inhibitors, which includes pembrolizumab and nivolumab. This paper analyzes the signals between PD-1 inhibitors and bullous pemphigoid based upon the reported real-world data. Methods : A pharmacovigilance analysis was performed on the publicly available Adverse Event Reporting System database of Food and Drug Administration. Disproportionality ratios were used to examine a signal between PD-1 inhibitors and bullous pemphigoid. A heat map was generated to depict the signal between PD −1 inhibitor use and skin toxicity adverse events. Results : The analysis indicated that there is a significant signal (PRR = 13.82 [95% CI: 9.99–19.11], Chi-squared with Yates' correction = 420.48) between pembrolizumab use and bullous pemphigoid and that there is a significant signal (PRR = 13.19 [95% CI: 10.57–16.46], Chi-squared with Yates' correction = 869.71) between nivolumab use and bullous pemphigoid. The signals remained statistically significant after stratifying for sex and age for both pembrolizumab and nivolumab. The signal is supported by 35 case reports in which there was evidence of PD-1 inhibitor use and a pemphigoid adverse event. Conclusion : When prescribing PD-1 inhibitors, physicians should monitor closely for symptoms of bullous pemphigoid.